PENGARUH PENGGUNAAN MEDIA PEMBALAJARAN POWERPOINT TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN KERTAUNGARAN - Kusnendar, Aris; Nanan Abdul Manan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by problems that occurred in class V at SDN Kertaungaran, namely that in using LCDs, teachers had not optimally utilized the infrastructure provided by the school. This is because teachers still teach using simple and easily available media, resulting in less than optimal student learning outcomes. The aim of this research is to determine the effect of power point media on student learning outcomes in class V science lessons at SDN Kertaungaran. The method used in this research is a quantitative method with a nonequivalent control group research design. Sampling in this research used a simple random sampling technique. The samples selected in this research were students of classes V A and V B. Data collection techniques used tests and documentation. Data analysis techniques use normality, homogeneity and paired sample t tests. The research results show a normality test > 0.05 which means the data is normally distributed and a homogeneity test with a result < 0.05 means the data is not homogeneous. The paired sample test obtained a calculated t value of 6.628 with a t table of 1.685. So according to the test decision it can be concluded that t count > t table, namely 6.628 > 1.685. The conclusion is that Ha is accepted and H0 is rejected, namely that there are differences in learning outcomes before and after implementing PowerPoint-based learning media.